MENGGALI MAKNA ASAS LEGALITAS DAN PERKEMBANGANNYA DI INDONESIA - Tahir, Ach. (UIN Sunan Kalijaga Yogyakarta, 2012)
The principle of legality is a fundamental principle in the Criminal Code and the Islamic Criminal Law. The Bill of Criminal Code of Indonesia recognizes the principle of material legality (not absolutely applicable). Then, the consequences, in spite of not regulated in legislation, are that the person‘s acts are worth to be convicted. The person can be convicted as based on living law in the community. The principle of legality in the positive law could be abandoned on condition that the crime threatens public order and security. In Islamic Criminal Law, the principle of legality could also be abandoned on condition that the crime threatens public order and security.